2016
DOI: 10.1038/celldisc.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

TRIB2 regulates normal and stress-induced thymocyte proliferation

Abstract: TRIB2, a serine/threonine pseudokinase identified as an oncogene, is expressed at high levels in the T-cell compartment of hematopoiesis. The proliferation of developing thymocytes is tightly controlled to prevent leukemic transformation of T cells. Here we examine Trib2 loss in murine hematopoiesis under steady state and proliferative stress conditions, including genotoxic and oncogenic stress. Trib2−/− developing thymocytes show increased proliferation, and Trib2−/− mice have significantly higher thymic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 62 publications
(85 reference statements)
2
37
0
Order By: Relevance
“…It is interesting to speculate that TRIBs may have a role in lineage decisions or phenotypic characteristics of myeloid and lymphoid leukemias, which may be determined by their specific cellular substrates. While it was shown that TRIB2 is a transcriptional target of the T cell transcription factor NOTCH1 [74], the absence of TRIB2 in a murine TRIB2-knockout model [75] was found to accelerate NOTCH1-driven T-ALL (Figure 5). This work also revealed a novel tumor suppressor-like function for TRIB2 in the cell cycle and proliferation of early T cell progenitor cells, and associated high levels of TRIB2 expression with early immature T-ALL and deregulated MAPK signaling [75].…”
Section: Tribbles Links To Cancer: a Corruption Of Cell Signaling?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to speculate that TRIBs may have a role in lineage decisions or phenotypic characteristics of myeloid and lymphoid leukemias, which may be determined by their specific cellular substrates. While it was shown that TRIB2 is a transcriptional target of the T cell transcription factor NOTCH1 [74], the absence of TRIB2 in a murine TRIB2-knockout model [75] was found to accelerate NOTCH1-driven T-ALL (Figure 5). This work also revealed a novel tumor suppressor-like function for TRIB2 in the cell cycle and proliferation of early T cell progenitor cells, and associated high levels of TRIB2 expression with early immature T-ALL and deregulated MAPK signaling [75].…”
Section: Tribbles Links To Cancer: a Corruption Of Cell Signaling?mentioning
confidence: 99%
“…While it was shown that TRIB2 is a transcriptional target of the T cell transcription factor NOTCH1 [74], the absence of TRIB2 in a murine TRIB2-knockout model [75] was found to accelerate NOTCH1-driven T-ALL (Figure 5). This work also revealed a novel tumor suppressor-like function for TRIB2 in the cell cycle and proliferation of early T cell progenitor cells, and associated high levels of TRIB2 expression with early immature T-ALL and deregulated MAPK signaling [75]. TRIB2 is cyclically expressed during the cell cycle and has the ability to promote the proteasomal degradation of the mitotic regulator CDC25C, which might explain some of the uncontrolled proliferation characteristics of leukemia [25].…”
Section: Tribbles Links To Cancer: a Corruption Of Cell Signaling?mentioning
confidence: 99%
“…It is known that TRIB2 is expressed in mammals. TRIB protein family members encode pseudo-kinase proteins that are highly conserved in evolution, and act as adaptors in signaling pathways for important cellular processes (6,7). Previous studies have focused on the pathological role of TRIB2 in various diseases, including CML, and metabolic and neurological diseases, in which it has been identified as a critical signaling modulator and mediator (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The connection of Trbl to Notch signaling is significant in light of the association of Tribs 2 and 3 in mammalian systems with Notch-dependent tumor formation (reviewed in Stein et al, 2015). Trib2 was identified as a downregulated gene upon g-secretase inhibitor treatment of Notch-dependent mouse T cell acute lymphoblastic leukemias cell lines, and the absence of Trib2 in a murine Trib2-knockout model was found to accelerate Notch1driven leukemias (Liang et al, 2016a;Stein et al, 2016). A correlation between Trib3 and Notch1 expression in lung adenocarcinoma cell lines led to work showing that Notch1 could be downregulated by the knockdown of Trib3 (Zhou et al, 2013).…”
Section: A Conserved Role For Trbl In Mediating E3 Ligase-dependent Nmentioning
confidence: 99%